A ROUTING AND SCHEDULING PROBLEM WITH HIERARCHICAL OBJECTIVES UNDER INDUSTRIAL LOGISTICS ENVIRONMENT: ANALYSIS, MODELING, AND TWO-PHASE HEURISTIC - Xu, Rui; Wu, Jiayan; Hong, Wenjing (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
This study investigates a routing and scheduling problem in industrial logistics that considers resource synchronization on heterogeneous facilities and maximum working duration. The problem calls for constructing routes and arranging the loading operations of dispatched vehicles on heterogeneous loading facilities while minimizing the total travel time first and balancing the workload second. We establish a mixed integer programming model and propose a two-phase heuristic. The first phase is to minimize total travel time by using a hybrid metaheuristic based on adaptive large neighborhood and variable neighborhood descent. The second phase is to balance the workload between different facilities with a post-optimization procedure. Extensive computational experiments demonstrate the effectiveness of our approach. In addition, we found that increasing the loading speed of facilities and extending the maximum working duration has a significant marginal decreasing effect in reducing total travel time, which can help enterprises optimize the allocation of logistics resources.